Patient Expectations about Communication in the Perioperative Setting of Elective Knee Surgery – a Questionnaire-based Cross-sectional Study - Walter, Sebastian G.; Naal, Florian; Impellizzeri, Franco M.; Moser, Berthold; Schildberg, Frank A.; Drobny, Tomas; Preiss, Stefan; Salzmann, Gian M. (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background Patient expectations are an issue which is attracting increased interest in outcome research for knee surgery procedures. So far, research into patient expectations has mainly focused on the procedure and postoperative functional improvements. The purpose of this study was to identify patient expectations in the perioperative setting.Material and Methods This was a single-center prospective study. A 17-item questionnaire (ordinal answer scale) about patientsʼ perioperative expectations was developed and completed by patients undergoing elective joint-preserving knee surgery. The study covered a period of 3 months and included all patients consecutively undergoing knee surgery. Subgroup analysis was performed for gender, age and type of insurance.Results 111 consecutive patients completed the questionnaire on admission. Significant preferences for one answer option were found for 13 out of 17 items. Patients considered it “unimportant” whether or not the physician wore a white coat during the consultation and “very important” that the first medical consultation after the patient was discharged from hospital was with the surgeon who had performed their operation. A concise explanation of the surgical procedure using images, talking to the surgeon the day before surgery and immediately after surgery, having their wound personally inspected by the surgeon, and, finally, the availability of the surgeon by phone were regarded as “important”. There were no differences in patient responses between the different subgroups.Conclusion Patients expect a high personal commitment and availability of the surgeon during the entire perioperative setting, starting from the first consultation and continuing during follow-up examinations.
Keywords: patient expectations; knee surgery; patient feedback; perioperative environment; relationships in healthcare